Tingkat Kecelakaan (Accident Rate) dan Hubungannya dengan Volume Lalu Lintas pada Ruas Jalan Tol Becakayu - Fiqry Ichsan Novriardo; Darmawan Pontan (Universitas Batanghari Jambi, 2026)
This study aims to analyze the traffic accident rate and its relationship with traffic volume on the Becakayu Toll Road during the 2020–2024 period. A quantitative research approach was employed using secondary data in the form of traffic volume data and accident records obtained from the Toll Road Operating Agency (BUJT) PT Kresna Kusuma Dyandra Marga. The data were analyzed on an annual basis by calculating the accident rate based on the standard number of accidents per 100 million vehicle-kilometers, with a section length of 16.78 km. The analytical methods included descriptive statistics, accident rate calculation, and Pearson correlation analysis to examine the relationship between Average Daily Traffic (ADT) and the number of accidents as well as the accident rate. The results indicate that an increase in traffic volume is followed by an increase in the number of accidents; however, the accident rate tends to fluctuate and shows a negative correlation with traffic volume. The correlation analysis reveals a very strong positive relationship between traffic volume and the number of accidents, as well as a strong negative relationship between traffic volume and the accident rate. These findings indicate a distinction between absolute accident frequency and relative risk per vehicle. Therefore, toll road safety evaluations should combine absolute accident indicators and exposure-based indicators to obtain a more comprehensive interpretation of traffic risk.